Gender and Living Situation-Based Sibling Rivalry: Solutions Through Family Counseling - Miswanto Miswanto; Nur Aini; Yuda Syahputra; Nur Arjani; Siti Mukminah Sinaga (UPT Publikasi dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2023)
Considering the high number of cases of sibling rivalry which can affect children's psychological health and family dynamics. This research aims to examine differences in sibling rivalry in terms of gender and living with parents or guardians (grandmother/siblings), as well as the implications of family counseling as an effort to prevent student sibling rivalry. This research is comparative research, the research sample was selected using random sampling technique. The research sample consisted of 241 students (25.7% men and 74.3% women). Data was collected using the sibling rivalry questionnaire (SRQ), which consists of 27 question items. Through the application of the RASCH model, the questionnaire was reviewed to determine internal consistency and measurement structure. The analysis technique uses descriptive analysis and Anova with the help of JASP Version 18.0. The results show there are significant differences between sibling rivalry based on gender and living together. In addition, female tend to behave in sibling rivalry at home compared to male. Further research is recommended to identify other factors that influence sibling rivalry, including economic conditions and parental education.____________________________________________________________Mengingat tingginya kasus sibling rivalry yang dapat mempengaruhi kesehatan psikologis anak dan dinamika keluarga. Penelitian ini bertujuan untuk menguji perbedaan sibling rivalry ditinjau dari gender dan tinggal bersama orang tua atau wali (nenek/saudara), serta implikasi konseling keluarga sebagai upaya pencegahan sibling rivalry siswa. Penelitian ini adalah penelitian komparatif, sampel penelitian dipilih dengan teknik random sampling. Sampel penelitian terdiri dari 241 siswa (25,7% laki-laki dan 74,3% perempuan). Data dikumpulkan dengan Sibling Rivalry Questionnaire (SRQ), yang terdiri dari 27 item pertanyaan. Melalui penerapan model RASCH, kuesioner ditelaah untuk menentukan konsistensi internal dan struktur pengukuran. Teknik analisis menggunakan analisis deskriptif dan Anova dengan bantuan JASP Version 18.0. Hasil menunjukkan ada perbedaan yang signifikan antara sibling rivalry berdasarkan gender dan tinggal bersama. Selain itu, perempuan cenderung berperilaku sibling rivalry ketika di rumah dibandingkan dengan laki-laki. Disarankan penelitian lebih lanjut untuk mengidentifikasi faktor-faktor lain yang mempengaruhi sibling rivalry, termasuk kondisi ekonomi dan pendidikan orang tua.